SEG Technical Program Expanded Abstracts 2014 2014
DOI: 10.1190/segam2014-1242.1
|View full text |Cite
|
Sign up to set email alerts
|

Making the most out of the least (squares migration)

Abstract: SUMMARYStandard migration images can suffer from migration artifacts due to 1) poor source-receiver sampling, 2) weak amplitudes caused by geometric spreading, 3) attenuation, 4) defocusing, 5) poor resolution due to limited source-receiver aperture, and 6) ringiness caused by a ringy source wavelet. To partly remedy these problems, least-squares migration (LSM), also known as linearized seismic inversion or migration deconvolution (MD), proposes to linearly invert seismic data for the reflectivity distributio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Previous research has shown that least-squares migration can be quite sensitive to velocity errors (Dutta et al, 2014a;Dutta and Schuster, 2014). This is because the model dimension is smaller than the data dimension, and the data can only be fitted when the background velocity allows for the correct positioning of structures in the image (Hou and Symes, 2016).…”
Section: Discussionmentioning
confidence: 98%
“…Previous research has shown that least-squares migration can be quite sensitive to velocity errors (Dutta et al, 2014a;Dutta and Schuster, 2014). This is because the model dimension is smaller than the data dimension, and the data can only be fitted when the background velocity allows for the correct positioning of structures in the image (Hou and Symes, 2016).…”
Section: Discussionmentioning
confidence: 98%
“…Using an inaccurate background model for LSM/ILSM can have a deleterious effect on the migration images (Dutta et al . ) and can lead to amplification of noise.…”
Section: Discussionmentioning
confidence: 99%
“…The NMO stacking velocity for the field data might be too crude to be used as a migration velocity model for certain parts of the data. Using an inaccurate background model for LSM/ILSM can have a deleterious effect on the migration images (Dutta et al 2014a) and can lead to amplification of noise.…”
Section: Discussionmentioning
confidence: 99%
“…For incomplete, undersampled or noisy data, emphasizing only the data misfit can lead to images that are degraded in quality with iterations because of over-fitting the noise. In the case of LSM, errors in the migration velocity model can also lead to defocusing of images with iterations (Dutta et al, 2014). However, the optimal estimation of λ is not trivial, and it may be more appropriate to reformulate the constrained optimization problem (1) as su e t to where Rm is a linear transform of the model vector, m, into a domain in which the prior suggests that the L2-norm should be minimized, is the tolerance/noise level for the data misfit and W is a weighting matrix.…”
Section: Methodsmentioning
confidence: 99%